Women directors, board attendance, and corporate financial performance - Jasmin Joecks; Kerstin Pull; Katrin Scharfenkamp (Corporate Governance: An International Review, 2023)
Research Question/Issue Using insights from an in-depth qualitative interview study, we propose an input-process-output model where the link between women directors (input) and corporate financial performance (output) is mediated by board attendance and where board attendance serves as a proxy of several intermediate but latent board processes. Further, we dig deeper into the nonlinearities of female boardroom representation by analyzing in how far the postulated mediation depends on the number of women in the boardroom. Research Findings/Insights Analyzing quantitative data from German supervisory boards over an 11-year period, we find the link between women directors and corporate financial performance to be partially mediated by board attendance, and we find the mediation to depend on whether there is more than just one “token” woman in the boardroom. When there is only one woman in the boardroom, her presence is positively linked to board attendance, but the higher board attendance does not to translate into a better corporate financial performance. Theoretical/Academic Implications Our study contributes to theory, by inductively enriching our understanding of how and when women directors and corporate financial performance are linked. Practitioner/Policy Implications Our study encourages firms to appoint more than one woman to the boardroom to profit from an enhanced board attendance that will then also translate into a better corporate financial performance.
Keywords: 320; board attendance; corporate governance; firm performance; tokenism; women directors